Best of the eLearning Guild's learning solutions : (Pfeiffer, 2008)
Contents: E-Learning strategy and management; Capturing skill and knowledge; Facilitating skill and knowledge transfer; Be constructive: blogs, podcasts, and Wikis as constructivist learning tools...